Using google forms as a learning evaluation tool in information and communication technology training for teachers - Warda Tuny (Balai Diklat Keagamaan Ambon, 2023)
This study aims to describe participants' responses or perceptions of the use of Google forms as an alternative learning evaluation tool in Information and Communication Technology (ICT) Technical Training for Madrasah Teachers in East Seram District. This type of research is qualitative research using the descriptive analysis method. Data collection was carried out using a questionnaire distributed to all participants, totaling 30 people. The results of the study show that learning evaluation using Google forms is very effective, there are no problems when using it, the access is fast, it is very easy to use and not complicated, and the results are very accurate so that the evaluation objectives can be achieved, it is also fun, efficient in terms of time and cost, so can be recommended for the facilitator to use it.